OXYGEN CONSUMPTION OF MUGIL MACROLEPIS IN RELATION TO DIFFERENT SALINITIES - Mathew, C V (Indian Journal of Fisheries, 2011)
The rate of oxygen consumption is an index of the metabolic activitiesof the fish. Several earlier workers (Job 1969, Fry 1947, Kinne 1964, Rao1965) have shown 'that in euryhaline species the environmental salinity to acertain extent influences respiration. The present study deals with the eflect ofsalinity on the respiratory rate of the tropical euryhaline fish Mugil macrolepis(Smith), a species useful for aquaculture.